Digitalization in Air Traffic Management and Enhancement of Personnel Training Technologies: Digitalisasi dalam Manajemen Lalu Lintas Udara dan Peningkatan Teknologi Pelatihan Personel - Shukurova Sabohat; Murodov Muhriddin (Academia Open, 2025)
General Background: The rapid advancement of digital technologies offers transformative possibilities for improving Air Traffic Management (ATM) and enhancing personnel training systems. Specific Background: In Uzbekistan, air navigation development is undergoing modernization, yet the adoption of advanced digital tools remains limited. Knowledge Gap: Despite global progress in digitalizing ATM, there is a lack of comprehensive evaluation on how digital tools impact both operational efficiency and the effectiveness of air traffic controller (ATC) training, particularly in developing aviation environments like Uzbekistan. Aims: This study aims to assess the integration of digital technologies in Uzbekistan’s ATM processes using a system modeling approach, focusing on operational improvements and training outcomes. Results: The findings demonstrate that AI-based decision support systems, real-time data analytics, radar automation, and virtual reality (VR) training platforms significantly enhance airspace safety, communication accuracy, and skill acquisition. System modeling, supported by MATLAB Simulink and Arena Simulation, revealed quantifiable improvements in traffic management efficiency and trainee performance. Novelty: This study provides the first systematic evaluation of digital ATM integration in Uzbekistan, offering empirical evidence on how these technologies align with ICAO and EUROCONTROL standards while addressing region-specific challenges. Implications: The results inform future policy directions, advocating for strategic digital adoption to modernize ATM infrastructure and improve ATC personnel readiness, with potential applicability to other developing aviation systems. Highlights: Digital technologies transform Air Traffic Management (ATM) and training systems. AI tools and VR training improve ATM efficiency and skill acquisition. Supports digital adoption for modernizing Uzbekistan's ATM and enhancing ATC readiness. Keywords: Air Traffic Management; Digitalization; System Modeling; Training Technology; Uzbekistan Aviation